Biosynthesis of cuprous oxide using banana pulp waste extract as reducing agent. (1st February 2021) - Torres-Arellano, S.; Reyes-Vallejo, O.; Pantoja Enriquez, J.; Aleman-Ramirez, J.L.; Huerta-Flores, A.M.; Moreira, Joel; Muñiz, Jesus; Vargas-Estrada, Laura; Sebastian, P.J.
Graphical abstract: Highlights: Cuprous oxide (Cu2 O) was synthesized via a green synthesis route employing banana extract. The green synthesis gave similar results in structure, morphology and optical properties as synthesis using glucose. The cuprite phase formed is oriented along the (1 1 1) plane and possesses octahedral phase. The Cu2 O synthesized possesses suitable structural, morphological and optical properties for photo-catalytic applications. Abstract: In this study we synthesized cuprous oxide by biosynthesis process, replacing conventional reducing agents like sodium borohydride (NaBH4 ), hydrazine (N2 H4 ) etc. with banana pulp waste extract. The particles obtained are highly oriented along the plane (1 1 1) and present octahedral morphology, which is excellent for electrical transport and photocatalytic degradation. TEM images show that particles are well crystallized and polycrystalline in nature with sizes in the range of 1–4 µm. According to FTIR spectra no remnants of banana pulp waste extract are present in the synthetized particles. The band gap calculated is 2.07 eV, which is suitable for solar conversion applications.